2013
DOI: 10.1021/ml400080t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Selective Nanomolar Inhibitors of the Human Neuraminidase, NEU4

Abstract: The human neuraminidase enzymes (hNEU) play important roles in human physiology and pathology. The lack of potent and selective inhibitors toward these enzymes has limited our understanding of their function and the development of therapeutic applications. Here we report the evaluation of a panel of compounds against the four human neuraminidase isoenzymes. Among the compounds tested, we identified the first selective, nanomolar inhibitors of the human neuraminidase 4 enzyme (NEU4). The most potent NEU4 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 31 publications
0
79
0
Order By: Relevance
“…43 A homology model of NEU4 was proposed to rationalize the binding of NEU4-selective inhibitors. 44 The binding epitope of NEU3 has been examined using a trisaccharide analog of GM3. 45 Some insight into the structure of hNEU can be gained from examining mutations of the enzymes.…”
Section: Structure Of Hneumentioning
confidence: 99%
See 2 more Smart Citations
“…43 A homology model of NEU4 was proposed to rationalize the binding of NEU4-selective inhibitors. 44 The binding epitope of NEU3 has been examined using a trisaccharide analog of GM3. 45 Some insight into the structure of hNEU can be gained from examining mutations of the enzymes.…”
Section: Structure Of Hneumentioning
confidence: 99%
“…The most potent and selective inhibitors for NEU4 were recently identied through only minor modications of DANA. 44 Albohy et al tested a set of compounds against all four hNEU which had previously shown only moderate activity in assays of NEU3 alone. 44 However, in testing against a panel of puried and recombinant hNEU, several of these compounds were found to have nanomolar activity against the NEU4 isoenzyme.…”
Section: Selectivity Of Inhibitors Among the Hneu Familymentioning
confidence: 99%
See 1 more Smart Citation
“…35 Installation of an azido group at C9 of Neu5Ac2en also provides a chemical handle for further modification to improve the selectivity for sialidase inhibitors. 36 We obtained a novel crystal structure of the catalytic domain of SpNanA in complex with 9-azido-9-deoxy-Neu5Ac2en (Neu5Ac9N 3 2en, 2 , Figure 1) (PDB accession code 5KKY) and compared this structure to its complex with Neu5Ac2en. 34 The Neu5Ac9N 3 2en binds to SpNanA in a similar way as Neu5Ac2en in other known structures, 18, 37 but surprisingly the SpNanA is a homodimer with Neu5Ac9N 3 2en in two different conformations in the active sites of two different subunits (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the insulin receptor by insulin was attenuated by inhibition of endogenous Neu1 by pretreatment with 1 mM DANA. Although DANA inhibits all mammalian sialidase isozymes 35,36 , sialidase isozyme-selective inhibitors have recently been developed for Neu1, Neu2, Neu3 and Neu4 [36][37][38][39][40] . Sialidase isozyme-selective inhibitors that do not inhibit Neu1 activity may thus be suitable for the treatment of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%